A mensagem recalcada: o mal-estar cultural em textos jornalísticos sobre violência - Candiani, Heci Regina (2007)
As a structural phenomenon affecting civilization, discontent is related to the difficulties of individuals in dealing with the demands imposed by living in societal settings. The concept of discontent refers to the conflict between individuals and peers, who are often taken as irreconcilable differents. This conflict can be seen in some claims for unlimited individual freedom, in the antagonism to established social rules, in the cravings for illiberal tendencies, in the yearnings for a repressive state, in the excessive physical and verbal hostility in routine tasks and in the indifference towards others. Such aspects of social relations have been widely assessed by sociology and are exposed in some standards of contemporary sociability. The objective is to understand how discontent mainly under the forms of exacerbated violence and of indifference can be placed into the Brazilian contemporary context and how can it be picked out in journalistic texts. The journalistic discourse consists of individual representation and reflects social relations rather than being a narrative that tries to re-enact objectively the facts. In this sense, it can be probed as a form of expressed discontent. This survey reviews, by means of depth hermeneutics, as proposed by John B. Thompson, texts of two Brazilian newspapers, Folha de S. Paulo and O Globo, covering cases of violence which occurred in São Paulo and Rio de Janeiro in 2004